Accelerating the Competency of Nagari Apparatus in Nagari Development Planning in Padang Pariaman Regency, Indonesia - Karyana, Ayi; Sari, Jayanti Armida; Sunarya, Amud (Jurnal Studi Pemerintahan, 2026)
This study examines the effect of accelerating village officials’ competencies on the quality of village development planning in Padang Pariaman Regency and identifies challenges in the planning process. Using a mixed-methods approach, quantitative data were collected through questionnaires administered to 79 village officials responsible for planning and analyzed using PLS-SEM, while qualitative data were obtained through in-depth interviews and analyzed thematically. The results indicate that officials’ competencies have a significant simultaneous effect on village development planning (R² = 61.3%); however, partially, only work experience shows a significant positive effect, whereas education and training do not. Qualitative findings reinforce that competencies are primarily developed through practical experience rather than formal education or non-continuous and less relevant training. Key challenges include limited human resource capacity, low training relevance, technical and technological constraints, and weak coordination and community participation. The study recommends continuous mentoring, needs-based training reform, and strengthened stakeholder collaboration to improve the effectiveness and sustainability of village development planning.